Mars Pater – in the Strategy of Constantine the Great - Bralewski, Sławomir (Studia Ceranea, 2024)
During his reign Constantine the Great sought protection of various gods, finally choosing the Christian God as his main protector. The iconographic material gathered from the mints remaining under his power in the early period of his rule shows that in the years 306–309 Constantine regarded Mars as his guardian deity. The author attempts to explain why the emperor sought Mars’s protection during that period and why he later began to look for a new divine guardian. This issue has not yet been properly explained in scholarly literature devoted to Constantine the Great.